Avaliação fenotípica e genotípica de segregantes de uma linhagem industrial de Saccharomyces cerevisiae - Ibelli, Flávia Danieli [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Fuel-ethanol fermentation process includes a reutilization of the yeast biomass, in which yeast cells are exposed tostress conditions as high temperature, increasing alcohol concentration and low pH values. This enviroment may cause a significant delay in fermentation and drop in cell viability. Some Saccharomyces cerevisiaestrains, however, have thermotolerance or resistance to higher ethanol concentrations, while being able to adapt to the environment in which they are. In this work, the industrial resistant yeast strain was isolated from fermented sugar cane at the end of the harvest to be good leavening. Aiming to study genetic features associated with cell resistance to sustained stress in an industrial yeast strain, they wereinduced to sporulation and the ascospores were dissected in order to generate homozygous derivatives andwere ramdomly selected for further phenotype analysis. The results have shown that two of segregating presented to be promising with the fermentative capacity and resistance to high temperature and ethanol concentration as compared to industrial strains PE-2, CAT-1 and SA-1. Following that,the real time PCR assay was performed to assess the relationship of APJ1, FPS1, MKT1, SWS2 and HSP12 genes with ethanol tolerance. Furthermore, was also analyzed the differential expression of the HSP12 gene as a molecular marker for stress-resistance in industrial yeast.The PCR was performed with two yeast strains: a resistant yeast (MA-12) and non-resistant (MA-139, ruled in the early experiments) and shows wich all genes evaluated revealed a significant expression in stress situations for the resistantstrain MA-12, which did not happen in the sensitive yeast (except for APJ1 gene), which shows that the selected genes are directly related to stress resistance. The results also suggest that HSP12 gene can be used as a molecular marker of stress in industrial yeast strains, since they have shown significant expression in the ...

O processo de fermentação para produção de álcool combustível inclui a reutilização da biomassa de levedura, situação em que as células de levedura são expostas a condições de estresse, como temperaturas elevadas, aumento da concentração de etanol e baixos valores de pH. Este processo pode ocasionar uma redução da viabilidade celular, diminuindo de forma significativa o rendimento da fermentação. Algumas linhagens de Saccharomyces cerevisiae, no entanto, apresentam termotolerância ou resistência a maiores concentrações de etanol, sendo capazes de se adaptar ao meio em que estão. Neste trabalho, uma linhagem de levedura industrial foi isolada da dorna de fermentação ao final de safra por apresentar capacidade de permanência no processo fermentativo e ser boa fermentadora. Com o intuito de avaliar quais genes estão envolvidos com essas características, a levedura isolada foi esporulada e dissecada para geração de novos segregantes, que foram analisados e selecionados quanto a termo e álcool resistência e capacidade fermentativa. Os resultados mostraram que dois dos segregantes avaliados apresentaram-se promissores com relação a capacidade fermentativa e resistência a altas temperaturas e concentrações de etanol quando comparados às linhagens industriais PE-2, CAT-1 e SA-1, largamente utilizadas nas usinas produtoras de etanol. Em seguida, foi realizado o ensaio de PCR em Tempo Real, para avaliar a relação dos genes APJ1, FPS1, MKT1, SWS2 e HSP12 com a tolerância ao etanol. Além disso, foi avaliado também a possibilidade do gene HSP12 ser um marcador molecular de estresse nas leveduras de linhagens industriais. Para isso, foram utilizadas duas linhagens de levedura: uma resistente ao etanol (MA-12) e não resistente (MA-139), excluída no início dos experimentos. Todos os genes avaliadosapresentaram expressão significativa nas situações de estresse para a linhagem resistente MA-12, o que não aconteceu...
Keywords: Saccharomyces cerevisiae; Etanol; Expressão gênica; Fermentação; Biotecnologia; Gene expression